The Potential of Nigella sativa oil on Clinical output improvement of diabetic neuropathy - Syuhada,, Kusnandar Anggadiredja, Neng Fisheri Kurniati, Akrom (Journal of Applied Pharmaceutical Science, 2023)
Diabetic neuropathy is a condition of impaired nerve function due to complications related to the development of diabetes through various mechanisms. Clinical improvement in diabetic neuropathy patients considers many clinical outcomes, so it requires a multitargeted approach to therapy. Nigella sativa oil is a natural ingredient traditionally used for various conditions related to diabetic neuropathy. It has been partially proven for various essential targets related to diabetic neuropathy, including as an antidiabetic, antidyslipidemic, antioxidant, anti-inflammatory, and neuroprotector. With its multicompound, multitarget capability, N. sativa has the potential as an additional herbal therapy in treating diabetic neuropathy. This review includes a description of diabetic neuropathy and the potential of N. sativa as adjunctive therapy in treating diabetic neuropathy.